2019
DOI: 10.3389/fpsyg.2019.02335
|View full text |Cite
|
Sign up to set email alerts
|

Two Reasoning Strategies in Patients With Psychological Illnesses

Abstract: Hyper-emotion theory states that psychological disorders are conditions in which individuals experience emotions that are appropriate to the situation but inappropriate in their intensity. When these individuals experience such an emotion, they are inevitably compelled to reason about its cause. They therefore develop characteristic strategies of reasoning depending on the particular hyper-emotion they experience. In anxiety disorders (e.g., panic attack, social phobia), the perception of a disorder-related th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…For example, accepting the risk of having left a gas tap open implies a lower focus on the possibility of a gas leak and an explosion and a greater focus on reassuring possibilities, such as having closed the tap securely and that the safety valves are activated. Furthermore, it also involves information processing that is less corroboratory and more refutatory than focusing on negative possibilities [ 51 ], thus providing reassuring information. This is achieved through the modification of four different patient assumptions: belief in the power to reduce threat, contamination, NJRE, doubt and uncertainty; that it is advantageous to invest in this direction; that this is morally necessary; and that, if not adhered to, suffering will increase, last a very long time, and create obstacles to normal daily activities [ 49 ].…”
Section: Methodsmentioning
confidence: 99%
“…For example, accepting the risk of having left a gas tap open implies a lower focus on the possibility of a gas leak and an explosion and a greater focus on reassuring possibilities, such as having closed the tap securely and that the safety valves are activated. Furthermore, it also involves information processing that is less corroboratory and more refutatory than focusing on negative possibilities [ 51 ], thus providing reassuring information. This is achieved through the modification of four different patient assumptions: belief in the power to reduce threat, contamination, NJRE, doubt and uncertainty; that it is advantageous to invest in this direction; that this is morally necessary; and that, if not adhered to, suffering will increase, last a very long time, and create obstacles to normal daily activities [ 49 ].…”
Section: Methodsmentioning
confidence: 99%
“…And in an anxious situation, compared with obsessive-compulsive individuals, anxious individuals with excessive anxiety showed greater con rmatory reasoning in reasoning about events (Gangemi et al, 2019), which also suggested that individuals with high anxiety would be more cautious in the face of negative information in the environment, expanding the generalization of negative information.…”
Section: Judgment Of Information -Reasoning Tasksmentioning
confidence: 97%
“…However, even in cases where negative preferences are present in normal, low-anxiety populations, studies still show that high-anxiety individuals tend to show a greater cognitive preference for negative emotional stimuli (Gangemi et al, 2013;Gangemi et al, 2019;Penninx et al, 2021;Reichenberger et al, 2015;Xun et al, 2021); for example, in a visual search task, high-anxiety people searched for negative stimuli faster than low-anxiety people (Byrne & Eysenck, 1995), and in the sentence judgment task, the implicit memory of threat words in high-anxiety group was much stronger than that in neutral words, but this phenomenon was not found in low-anxiety group (Lang & Craske, 1997). However, research on positive emotions has had mixed results.…”
Section: Introductionmentioning
confidence: 99%
“…The first is to facilitate the acceptance of ERP exercises and increase the motivation to implement them. The second is justified by the fact that if a threat is accepted, the protective investment is reduced and, within this, the hyperprudent cognitive orientation, thus increasing the possibility that corrective information of the threat perception can really be taken into consideration by the patient (76,77). At the same time ERP is introduced.…”
Section: Treatmentmentioning
confidence: 99%